Pengembangan Produk Olahan Buah Mangrove Jenis Api-Api (Avicennia Spp) Di Kelompok Kreasi Mangrove Lestari Kelurahan Margomulyo Balikpapan - Rahmawaty, Patria; Zulkifli, Zulkifli; Amaliah, Nur; Hermansyah, Hadi; Mulyani, Yogiana (Universitas Nusantara PGRI Kediri, 2018)
Problems faced by Mangrove Creation Group Lestari is a black mangrove fruit flour caused by the process of less rapid that is drying is too long and during the process of grinding, still simply, that is using a blender. While the blender can only accommodate small capacity and this will inhibit the process of processing raw materials into processed products. The method used in solving the problem of Sustainable Mangrove Creation Group is by socializing the processing process of mangrove flour according to standard, providing flour grinding tool to get good quality flour, and demostration processing of mangrove flour into snack and cake. Based on the results of socialization of community service in Kelurahan Margomulyo can be successful because it sees the enthusiasm of Margomulyo Kelurahan who get the knowledge related to the processing of mangrove fruit flour according to the standard, able to apply or use the disk miller, and the community get standard recipe from swissroll flour mangrove and cimi-cimi mangrove fruit flour.